Cost-benefit analysis of trading strategies in the stock index futures market - Xiong Xiong; Yian Cui; Xiaocong Yan; Jun Liu; Shaoyi He (Financial Innovation, 2020)
With the introduction of many derivatives into the capital market, including stock index futures, the trading strategies in financial markets have been gradually enriched. However, there is still no theoretical model that can determine whether these strategies are effective, what the risks are, and how costly the strategies are. We built an agent-based cross-market platform that includes five stocks and one stock index future, and constructed an evaluation system for stock index futures trading strategies. The evaluation system includes four dimensions: effectiveness, risk, occupation of capital, and impact cost. The results show that the informed strategy performs well in all aspects. The risk of the technical strategy is relatively higher than that of the other strategies. Moreover, occupation of capital and impact cost are both higher for the arbitrage strategy. Finally, the wealth of noise traders is almost lost.
Keywords: 650; Trading strategy; Stock index futures; Agent-based model; Cost-benefit analysis